2013
DOI: 10.1111/jrh.12022
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Disparities in Patient Travel for Dialysis in the United States

Abstract: Purpose: To estimate travel distance and time for US hemodialysis patients and to compare travel of rural versus urban patients.Methods: Dialysis patient residences were estimated from ZIP code-level patient counts as of February 2011 allocated within the ZIP code proportional to census tract-level population, obtained from the 2010 US Census. Dialysis facility addresses were obtained from Medicare public-use files. Patients were assigned to an "original" and "replacement" facility, assuming patients used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…We found that patients live, on average, 4 miles from their chosen dialysis facility and less than 2 miles to the nearest dialysis facility. Our work was consistent with previous studies that showed urban patients on hemodialysis do not travel far to their dialysis centers [6, 7, 42]. Having dialysis facilities close to where patients need them is a significant accomplishment, yet to be attained in rural areas in the US and in many other countries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that patients live, on average, 4 miles from their chosen dialysis facility and less than 2 miles to the nearest dialysis facility. Our work was consistent with previous studies that showed urban patients on hemodialysis do not travel far to their dialysis centers [6, 7, 42]. Having dialysis facilities close to where patients need them is a significant accomplishment, yet to be attained in rural areas in the US and in many other countries.…”
Section: Discussionsupporting
confidence: 92%
“…For many patients with end-stage renal disease (ESRD), distance from their dialysis facility may be particularly important due to the thrice weekly hemodialysis treatment requirement. Two US studies have shown that most people in urban areas live within 30 minutes of their dialysis facility and that longer travel time was associated with greater mortality and worse health related quality of life [6, 7]. However, to our knowledge, no study has examined racial disparities in proximity to dialysis facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Distances between a patient’s home and primary care practice may be acceptable for occasional, intermittent visits; however long travel distances for a short 15 min MOB visit may be problematic, a barrier that can be compounded by weather-related concerns. Distance is known to be an important factor in seeking healthcare in rural veterans [37] and other populations [3842], increasing the risk of not returning for care. Inequalities to access to care have even been observed elsewhere, including Japan [43].…”
Section: Implementation Challenges Of the Medicare Obesity Benefit Inmentioning
confidence: 99%
“…The small sample within each category of our exposure variable caused many of our estimates to be imprecise; however, we focused on an issue that has been sparsely addressed in the literature. Studies looking at geographic disparities in use of medical help have focused on other health outcomes or access to only specialized care for becoming pregnant . Another limitation was that we were constrained to women's place of residence at the time of the interview, which on average, was 9 years after the age at visiting a doctor for help getting pregnant.…”
Section: Discussionmentioning
confidence: 99%